MOPSO approach for FACTS device installation in power system - Jumaat, Siti Amely (2013)
This paper presents an approach to sigma multiobjective optimization particle swarm (o-MOPSO) technique for optimal allocation of Flexible AC Transmission System (FACTS) devices. For this study, Static Var Compensator (SVC) is selected as a compensation device. Proposal o-MOPSO technique has been implemented to minimize the transmission losses and the cost of investment in the system. Simulations performed on standard IEEE RTS 30-bus and IEEE 118-bus RTS. Results are compared with those obtained from the programming of multiobjective evolutionary technique (MOEP) in order to highlight its advantages.